2006
DOI: 10.1002/ceat.200600093
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Heat Transfer Prediction in a Corrugated Plate Heat Exchanger using a CFD Code

Abstract: The purpose of this study is to explore the potential of using a general purpose CFD code to compute the characteristics of the flow field, and of the heat transfer augmentation in conduits with corrugated walls, encountered in commercial plate heat exchangers (PHE). The CFD code is used to simulate the performance of a PHE model comprised of stainless steel plates, following a herringbone design and assembled for single-pass countercurrent flow. The code is validated by comparing the numerical results with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 13 publications
2
39
0
1
Order By: Relevance
“…By plotting the friction coefficient and the Nusselt number as functions of the Reynolds number they found that the transition from laminar to turbulent conditions occurs at Re % 300. Kanaris et al [17] calculated the steady-state flow field between three corrugated plates and obtained good agreement with experimental values. They found that the Nusselt number and the friction coefficient increase with the Reynolds number.…”
Section: Introductionmentioning
confidence: 56%
“…By plotting the friction coefficient and the Nusselt number as functions of the Reynolds number they found that the transition from laminar to turbulent conditions occurs at Re % 300. Kanaris et al [17] calculated the steady-state flow field between three corrugated plates and obtained good agreement with experimental values. They found that the Nusselt number and the friction coefficient increase with the Reynolds number.…”
Section: Introductionmentioning
confidence: 56%
“…Many studies have been carried out on channels provided with grooves [21][22][23][24], and geometries with obstructions, more similar to the profiled membranes, applied for passive micromixers [25][26][27][28][29] Moreover, several papers can be found in the literature on hydrodynamics and heat transfer predictions via Computational Fluid Dynamics (CFD) in corrugated channels, mainly with reference to heat exchangers [30][31][32][33][34], but very few woks have been devoted to mass transfer phenomena in such geometries. Zhang [35] carried out CFD modelling of fluid flow and mass transfer in a crosscorrugated triangular duct by simulating water vapour transport in dry air; correlations of friction factor and Sherwood number with the Reynolds number were proposed.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Kanaris et al [3] studied the capability of a general purpose commercial CFD code to predict the flow and heat transfer characteristics of a cross-corrugated plate. They used the SST model as the most appropriate turbulence model.…”
Section: Introductionmentioning
confidence: 99%